2008
DOI: 10.1017/s0029665108008665
|View full text |Cite
|
Sign up to set email alerts
|

Session 1: Public health nutrition Breast-feeding practices in Ireland

Abstract: Breast-feeding is the superior infant feeding method from birth, with research consistently demonstrating its numerous short-and long-term health benefits for both mother and infant. As a global recommendation the WHO advises that mothers should exclusively breast-feed for the first 6-months of life, thus delaying the introduction of solids during this time. Historically, Irish breast-feeding initiation rates have remained strikingly low in comparison with international data and there has been little improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 64 publications
(85 reference statements)
0
21
1
Order By: Relevance
“…Embarrassment is often cited as one of the major reasons for not choosing to breastfeed or for early breastfeeding discontinuation . A society that is perceived by women to disapprove of breastfeeding in public is not conducive to prolonged breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Embarrassment is often cited as one of the major reasons for not choosing to breastfeed or for early breastfeeding discontinuation . A society that is perceived by women to disapprove of breastfeeding in public is not conducive to prolonged breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting factors for EIBF include: place of residence and delivery [12]; postnatal care and educational status [9]; unemployment benefit, social welfare and household income [13]; maternal age and socioeconomic status [14]; marital status, smoking, breastfeeding exposure [15]; parity [16]; and antenatal care [17]. Conversely, a prospective study done in India discovered parental education, living condition, number of antenatal visits, birthweight, cultural habit of the population, postnatal breastfeeding advice, previous breastfeeding exposure, and mother’s employment had no significant association with EIBF [18].…”
Section: Introductionmentioning
confidence: 99%
“…The literature, however, suggests that predictors of breastfeeding may vary in different parts of the world. For instance, studies in Australia, Iceland, Ireland, Scotland, as well as the USA have found that breastfeeding rates are higher among women who are older and have higher levels of education (Baghurst et al, 2007; Cairney & Barbour, 2007; Tarrant & Kearney, 2008; Taylor, Risica, Geller, Kirtania, & Cabral, 2006; Thome, Alder, & Ramel, 2006). Additionally, higher incomes have also been associated with increased breastfeeding rates in areas such as Sweden (Wallby & Hjern, 2009), and rural Jamaica (Chatman et al, 2004).…”
mentioning
confidence: 99%